Heterologous DNA-prime/protein-boost immunization with a monomeric SARS-CoV-2 spike antigen redundantizes the trimeric receptor-binding domain structure to induce neutralizing antibodies in old mice - Pflumm, Dominik; Seidel, Alina; Klein, Fabrice; Groß, Rüdiger; Krutzke, Lea; Kochanek, Stefan; Kroschel, Joris; Münch, Jan; Stifter, Katja; Schirmbeck, Reinhold (Frontiers in Immunology, 2023)
A multitude of alterations in the old immune system impair its functional integrity. Closely related, older individuals show, for example, a reduced responsiveness to SARS-CoV-2 vaccines. However, systematic strategies to specifically improve the efficacy of vaccines in the old are missing or limited to simple approaches like increasing the antigen concentration or injection frequencies. We analysed whether the intrinsic, trimeric structure of the SARS-CoV-2 spike (S) antigen and/or a DNA- or protein-based antigen delivery platform affects priming of functional antibody responses particularly in old mice. S-antigens were primarily defined by the presence/absence of the membrane-anchoring TM-domain and the closely interlinked formation/non-formation of a trimeric structure of the receptor binding domain (S-RBD). Among others, we generated vectors expressing prefusion-stabilized, cell-associated (TM+) trimeric ´S2-P´ or secreted (TM-) monomeric ´S6-PΔTM´ antigens. These proteins were produced from vector-transfected HEK-293T cells under mild conditions by Strep-tag purification, revealing that cell-associated but not secreted S-proteins tightly bound Hsp73 and Grp78 chaperones. Both TM-deficient S6-PΔTM and full-length S2-P antigens elicited very similar S-RBD-specific antibody titers and pseudovirus neutralization activities in young (2-3 months) mice. In contrast, the trimeric S2-P but not the monomeric S6-PΔTM antigen induced a high S-RBD-specific antibody response in old (23-24 months) mice through homologous DNA-prime/DNA-boost or protein-prime/protein-boost vaccination. However, old mice efficiently elicited a S-RBD-specific antibody response after heterologous DNA-prime/protein-boost immunization with the S6-PΔTM antigen and antibody titers even reached similar levels and neutralizing activities as in young mice and also cross-reacted with different S-variants of concern. The old immune system thus distinguished between trimeric and monomeric S-protein conformations: it remained antigen-responsive to the trimeric S2-P antigen and a simple change in the vaccine delivery regimen was sufficient to unleash its reactivity to the monomeric S6-PΔTM antigen. This clearly shows that both the antigen structure and the delivery platform are crucial to efficiently prime humoral immune responses in old mice, and might be relevant for designing ´age-adapted´ vaccine strategies.